Living Values Education: An Inter-generational Transition (Research Journal on Multi-disciplinary Issues, 2021)
This study was carried out to flourish the perception and experiences of living values in an intergenerational context. This article included the research question comprising intergenerational retina to retrieve the reality of relational transition in the community. For the research question, I have presented participants perceived living values in their practical life stories. Research participants were the people from six families including three different age groups, viz, 13-19, 20-59 and 60 plus. The study is qualitative and mainly guided by need, Social Integration, Hybridization, Construction and Deconstruction theory. Here I have attempted to show the linking influence of education on living values in this current Nepalese education system.